2015
DOI: 10.3109/08923973.2015.1063645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of venom immunotherapy on serum level of CCL5/RANTES in patients withHymenopteravenom allergy

Abstract: Hymenoptera venoms are known to cause life-threatening IgE-mediated anaphylactic reactions in allergic individuals. Venom immunotherapy is a recommended treatment of insect allergy with still the mechanism not being completely understood. We decided to assess the serum CCL5/RANTES level in patients who experienced severe anaphylactic reaction to Hymenoptera venom and to find out changes in the course of immunotherapy. Twenty patients (9 men, 11 women, mean age: 31.91 ± 7.63 years) with history of anaphylactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…The natural ligands for CCR5 are macrophage inflammatory protein 1α (MIP1α/CCL3), MIP1β/CCL4, and regulated upon activation, normal T‐cell expressed, and secreted (RANTES/CCL5). CCL5/RANTES serum concentration is elevated in insect venom‐allergic patients compared to healthy individuals and decreases significantly during the course of AIT . CCR5 is involved in chemotaxis of immune cells to inflammatory sites in the periphery .…”
Section: Discussionmentioning
confidence: 99%
“…The natural ligands for CCR5 are macrophage inflammatory protein 1α (MIP1α/CCL3), MIP1β/CCL4, and regulated upon activation, normal T‐cell expressed, and secreted (RANTES/CCL5). CCL5/RANTES serum concentration is elevated in insect venom‐allergic patients compared to healthy individuals and decreases significantly during the course of AIT . CCR5 is involved in chemotaxis of immune cells to inflammatory sites in the periphery .…”
Section: Discussionmentioning
confidence: 99%
“…27 Two AITinduced chemokines, CCL-5 (RANTES), and CCL-23 (MIP3), which are known to be involved in macrophage chemotaxis and were reported to be elevated in serum samples of patients receiving (insect venom) immunotherapy, were also detected in-and off-season. 28 CCL-5 is a major regulator of suppressive immune programs 29 and may contribute to antagonize pro-allergic type-2 immunity by recruiting Th1 cells as well as regulatory T cells. 30 The atypical chemokine receptor ACKR2, 30 the major CCL-5 scavenger receptor, is decreased through AIT and further increases the biological activity of CCL5.…”
Section: Ait-induced Local Changes In Off-seasonmentioning
confidence: 99%
“…In considering the increase of eosinophils in the circulation during the initial phase of VIT we assume that CCL5/RANTES and DCs' cytokines may result in the eosinophil response. It has been reported by Gawlik et al [32] that the chemokine level was significantly reduced after 6 days of rush venom immunotherapy. Our observations have shown that in patients treated with bee venom the CCL5/RANTES concentration increased after venom administration (p = 0.39).…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported by Gawlik et al . [ 32 ] that the chemokine level was significantly reduced after 6 days of rush venom immunotherapy. Our observations have shown that in patients treated with bee venom the CCL5/RANTES concentration increased after venom administration ( p = 0.39).…”
Section: Discussionmentioning
confidence: 99%